The effect of grouping on achievement, classroom participation and interaction of students in modern geometry at the Manuel L. Quezon (Public) High School, Manila - De Leon, Lorenzo Padua 1918- (1972)
The effects of two different methods of grouping on the achievement of students and on their participation and interaction in the classroom were compared in this study. There was a significant difference in the achievement of the students in the specific ability group from those of the general ability group. Those in the specific ability group achieved better.